An overlooked fact: thrombocytopenia following bioprosthetic aortic valve replacement - Kizilay, Mehmet (Kardiochir Torakochirurgia Pol, 2019)
INTRODUCTION: Thrombocytopenia observed after bioprosthetic aortic valve replacement has remained a puzzle to solve. AIM: To analyze thrombocytopenia occurring after bioprosthetic aortic valve replacement by comparison to mechanical aortic valve replacement and coronary artery bypass grafting procedures. MATERIAL AND METHODS: The study was conducted retrospectively on a total of 297 patients who underwent bioprosthetic aortic valve replacement, mechanical prosthetic aortic valve replacement and coronary artery bypass grafting at the cardiovascular surgery department of our clinical center between January 2013 and September 2017. Preoperative and postoperative first 14-day thrombocyte levels of the patients were analyzed. RESULTS: The postoperative blood thrombocyte level decrease was found to be more significant in patients who underwent bioprosthetic aortic valve replacement than in patients who underwent mechanical aortic valve replacement and coronary artery bypass grafting (p < 0.01). There was also a statistically significant difference in the time to reach the lowest postoperative platelet levels according to type of surgery (p = 0.001; p < 0.01). CONCLUSIONS: When compared to the patients who underwent coronary artery bypass grafting and mechanical prosthetic aortic valve replacement, postoperative thrombocytopenia was found to be more severe in patients who underwent bioprosthetic aortic valve replacement, with a dramatic decrease in thrombocyte count being observed on the postoperative second day. It was found that the thrombocytopenia recovers without causing any problem. We think that the shear forces may play a role in this recovery through washout of chemicals responsible for thrombocytopenia from the glutaraldehyde treated bioprostheses.